Femtosecond laser inscribed Mach-Zehnder Interferometer: a compound all-in-fiber versatile sensing device - Ioannou, Andreas; Theodosiou, Antreas; Caucheteur, Christophe; Kalli, Kyriacos (My University, 2020)
We consider the sensing characteristics of a compact all-in-fiber Mach-Zehnder interferometer (MZI) inscribed using a femtosecond laser. The structure was created in the cladding of a single-mode optical fiber close to the cladding-air interface (<5μm gap) to deviate light from the core and encourage evanescent field interaction with the fiber’s surroundings. This compact device features a refractive index sensitivity beyond 5000 nm/RIU in aqueous solutions. Two fiber Bragg gratings (FBGs) were also manufactured, one in the pristine fiber core and the other in the cladding MZI and are monitored for sensing purposes. We used the plane-by plane (Pl-by-Pl) fabrication method, ensuring reliability and repeatability in the sensor development, as all gratings and MZI were inscribed with the same femtosecond laser parameters. We focus on the device response to changes in temperature, strain, bend, surrounding refractive index and relative humidity. By combining the compound sensor with a core FBG we produced a device capable of measuring multiple parameters using the same demodulation equipment, whilst simultaneously enhancing and individually separating each measurand of interest.
Keywords: Cladding components; Femtosecond laser inscription; Fibre Bragg gratings; Fibre optics sensors; Microstructure fabrication; Optical design and fabrication